Thermal stability of nano RTV vs. RTV coatings in porcelain insulators. (1st December 2020) - Taghvaei, Monire; Sedighizadeh, Mostafa; NayebPashaee, Nasim; Sheikhi Fini, Alireza
Highlights: Thermal decomposition of RTV containing ZnO/ S i O 2 Hybrid nanoparticles were studied. ZnO and S i O 2 nanoparticles were modified with APTES and HMDS as coupling agent. Surface modification was verified through experimantal analysis; and. Thermal behavior of two different types of nano RTV composites and pure RTV was compared through OFW method. Abstract: Porcelain enjoys high thermal stability and its characteristics determine the life span of porcelain coated insulators in transmission power lines especially under harsh environmental conditions. In addition, room temperature vulcanized (RTV) silicone rubber coating is a reliable maintenance approach to improve performance and lifetime of porcelain insulators. On the other hand, thermal decomposition behavior of polymeric material significantly influences their aging process and there are many studies on enhancement of nanocomposites specifications by adding different types of nanoparticles. In this paper two different types of silicon rubber RTV nanocomposites with low content of modified nano ZnO and nano S i O 2 particles and pure RTV were compared in terms of their thermal behavior. Modification of nanoparticles and preparation of the coatings were carried out and the products were submitted to different experimental tests. Also, the activation energy was calculated from thermogravimetric analysis (TGA) test as an important factor in thermal aging of nanocomposites. Results of the study suggested that activation energy in the nano ZnO and ZnO/ S i O 2 composites increased in comparison with the pure RTV. This can confirm thermal aging enhancement of the nano RTV in comparison with the pure RTV and can prove helpful in estimating the expected lifetime of the coatings, which is valuable in estimating the reliability of porcelain insulators.